Changes in c‐erbB‐2 Immunoexpression in Feline Endometrial Adenocarcinomas. Issue 1 (7th December 2015) - Saraiva, AL; Payan‐Carreira, R; Gärtner, F; Faria, F; Lourenço, LM; Pires, MA
Contents: Human epidermal growth factor receptor type 2 (c‐erbB‐2), an oncoprotein with potential prognostic marker and therapeutic use, is overexpressed in several human and animal tumours. But information regarding this molecule in feline tumours is scarce. This study aimed to assess the changes in the immunohistochemical expression of c‐erbB‐2 in feline endometrial adenocarcinomas (FEA) compared to normal endometrium. An immunohistochemistry assay using a specific antibody against c‐erbB‐2 was performed in FEA samples (n = 34) and in normal endometrium in the follicular (FS; n = 12) and luteal (LS; n = 11) stages. In FEA, the c‐erbB‐2 immunoexpression was assessed in neoplastic epithelial cells whilst in normal endometria it was individually evaluated in the surface and the superficial and deep glandular epithelia (SE, SGE and DGE, respectively). In FS and in LS, all the epithelia were positive for c‐erbB‐2; positivity was higher in the SE and the SGE than in DGE. Twenty of the 34 FEA samples (58.8%) were positive for c‐erbB‐2 immunolabelling. Nevertheless, its expression was higher in all the epithelia in the FS compared to FEA (p ≤ 0.0001) or the LS (p = 0.016). The results presented herein suggest that c‐erbB‐2 molecule is differently expressed in the feline endometrium through the oestrous cycle and though it may also be involved in feline endometrial carcinogenesis, a question remains unanswered on the importance of additional pathways of epithelial proliferation in the neoplastic changes in feline endometrium.